2016
DOI: 10.1002/acp.3213
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Uncertainty through Disagreement

Abstract: This study explored the association between different types of brief disagreements and subsequent levels of expressed psychological uncertainty, a fundamental cognitive aspect of complex problem solving. We examined 11 hours (11 861 utterances) of conversations in expert science teams, sampled across the first 90 days of the Mars Exploration Rover mission. Utterances were independently coded for micro-conflicts and expressed psychological uncertainty. Using time-lagged hierarchical linear modeling applied to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 79 publications
(140 reference statements)
0
5
0
Order By: Relevance
“…Content disagreements can enhance team learning and effective problem solving (e.g., Kellermanns et al, 2008;Paletz, Chan, & Schunn, 2016). However, disagreement is a complex phenomenon embedded in temporal interaction dynamics and influenced by attributes of behaviors, individuals, and teams.…”
Section: Discussionmentioning
confidence: 99%
“…Content disagreements can enhance team learning and effective problem solving (e.g., Kellermanns et al, 2008;Paletz, Chan, & Schunn, 2016). However, disagreement is a complex phenomenon embedded in temporal interaction dynamics and influenced by attributes of behaviors, individuals, and teams.…”
Section: Discussionmentioning
confidence: 99%
“…Both team disagreement and individual uncertainty rise and fall naturally over the course of conversations (Ball & Christensen, 2009;Chan et al, 2012;Christensen & Ball, 2016b;Paletz, Chan, & Schunn, 2016;Paletz, et al, 2011;McDonnell, 2012). Prior research on interactions between social and cognitive processes has often found important correlations between temporal dynamics of social/cognitive processes (e.g., conflicts sparking analogies during conversation; Paletz, Schunn & Kim 2013).…”
Section: Research Questions About Uncertainty and Conflict In Design mentioning
confidence: 99%
“…Providing some answers to the repeated calls for more dynamic research on team processes (e.g., Kozlowski, 2015 ) and on leader-follower interactions (e.g., Dinh et al, 2014 ), a number of recent studies have adopted a temporal approach and begun to study actual behavioral interactions in the workplace (e.g., Meinecke, Lehmann-Willenbrock, & Kauffeld, 2017 ; Paletz, Chan, & Schunn, 2016 ; Zijlstra, Waller, & Phillips, 2012 ). In particular, a small but growing research base investigates actual behaviors and behavioral patterns embedded in workplace interactions.…”
mentioning
confidence: 99%